John Rawls: uma teoria da justiça e o liberalismo - Zvirblis, Alberto Antonio (2009)
This dissertation is based on the distributive justice theory of John Rawls. It has the purpose of stressing that the theory of justice as fairness supports, in contemporary world, the maximization in the distribution of primary goods which are essential to human dignity in favor of the least fortunate, who are in the worst position in the social ladder, without jeopardizing the inviolability of individuality, which for Rawls is essential: ―Each person possesses an inviolability founded on justice that even the welfare of society as a whole cannot override.‖ Rawls equitable justice stems from original position, which is contractualist, in that the parties are placed behind the veil of ignorance, with no knowledge of the external world and the social position of each participant, in order to permit the founding of principles of justice that are impartial. , the present dissertation seeks to contribute to the understanding that the theory of justice establishes, in the original position, the principles of justice which all agree with and accept to live under a cooperative liberal democratic system, convinced that the primary goods, increasingly scarce in the face of a growing demand and nobody willing to accept a smaller share, will be distributed in an equitable manner, maximizing the distribution to the least endowed in society